A History of the Church - Hughes, Philip, 1895-1967 (Sheed and Ward, 1947)
Contenido: Volumen 2: The Church and the World the Church Created [La Iglesia y el mundo que la Iglesia creó] y Volumen 3: The Revolt against the Church: Aquinas to Luther [La rebelión contra la Iglesia: de Tomás de Aquino a Martín Lutero]. Falta el volumen 1: The Church and the World in which the Church Was Founded [La Iglesia y el mundo en que la Iglesia fue fundada].